NUCLEOLAR CHROMOSOME VARIANTS IN STERNOPYGUS-MACRURUS (PISCES, STERNOPYGIDAE) FROM 3 BRAZILIAN RIVER BASINS - Dealmeidatoledo, L. F.; Foresti, F.; Daniel, MFZ; Toledofilho, S. D. (Univ Florence Botany Inst, 1993)
The karyotypes, location of nucleolus organizer regions (NOR) and constitutive heterochromatin pattern of Sternopygus macrurus (Pisces, Gymnotoidei) of natural populations from the Amazon River, Sao Francisco River and Tiete River (the last belonging to the Upper Parana River system) are reported. All specimens had 2n = 46 chromosomes and presented small differences in karyotypic formulae, but populations of each river basin had a different fixed NOR phenotype. The loss of the satellite and a gradual deletion of the heterochromatin block adjacent to the NOR may be the origin of the variants. The possible mechanism of fixation of the NOR phenotypes, and the implications of the occurrence of intraspecific differences in fixed NOR phenotype in this species are discussed.
Keywords: FISH CYTOGENETICS; NOR; C-BAND; STERNOPYGUS; GYMNOTOIDEI